FACTORS INFLUENCING SECOND LANGUAGE ACQUISITION - Siti Khasinah (Englisia: Journal of Language, Education, and Humanities, 2014)
Motivation, attitude, age, intelligence, aptitude, cognitive style, and personality are considered as factors that greatly influence someone in the process of his or her second language acquisition. Experts state that those factors give a more dominant contribution in SLA to learners variedly, depend on who the learners are, their age, how they behave toward the language, their cognitive ability, and also the way they learn.